Murabahah Financing And Musyarakah Financing Applications At “Bank JT Sharia” - Haidar Tri Putra; Azzah Afifah Huwaina (Journal of Economics, Social, and Humanities, 2023)
According to OJK, Sharia banks are banks that operate under Sharia Principles. The implementation of sharia principles is the main differentiator from conventional banks. With the growing rivalry in the banking industry, banks must continue to offer top-notch services and broaden their product offerings to meet consumer demand. This study investigates the application of sharia accounting to mudarabah and musyarakah loans at Sharia Bank JT based on PSAK No. 102 and PSAK No. 106. The discussion focuses on murabahah and musyarakah lending practices at Bank Jaten Syariah. This research uses a qualitative descriptive method using data from financial reports and direct interviews. Research findings show that the implementation of muharabah and musyarakah loans at Sharia Bank JT is under PSAK 105 and 106, with various adjustments to the provisions issued by the Financial Services Authority.